The Non-transcriptional Function of IRF3 Dynamically Regulates Immune Cell Populations in Acute on Chronic Ethanol in Mice - E. Nagy, Laura; Garcia Sanz, Carlos; Poulsen, Kyle; R McMullen, Megan; Chattopadhahay, Saurabh; Sen, Ganes (Revista Cubana de Investigaciones Biomédicas, 2020)
Introduction: Interferon regulatory factor 3 (IRF3) is a transcription factor mediating anti-viral responses, yet recent evidence indicates that IRF3 also has critical non-transcriptional functions, including activating RIG-I-like receptors-induced IRF-3-mediated pathway of apoptosis (RIPA) and restricting activity of NFκB. Using a novel murine model expressing only non-transcriptional IRF3 activity (Irf3S1/S1), we tested the hypothesis that non-transcriptional functions of IRF3 modulate innate immune responses in the Gao-binge (acute on chronic) model of alcohol-related liver disease. Objective: To prove that non-transcriptional functions of IRF3 modulate innate immune responses in the Gao-binge (acute on chronic) model of alcohol-related liver disease. Material and Methods: C57BL/6, Irf3-/- and Irf3S1/S1 were exposed to Gao-binge ethanol-induced liver injury. IRF3-mediated RIPA was investigated in cultured macrophages. Results: Phospho-IRF3 and IRF3-mediated signals were elevated in livers of patients with alcoholic hepatitis. In C57BL/6 mice, Gao-binge ethanol exposure activated IRF3 signaling and resulted in hepatocellular injury. Indicators of liver injury were differentially impacted by Irf3genotype. Irf3-/-, but not Irf3S1/S1, mice were protected from steatosis, ALT/AST and inflammatory cytokine expression. In contrast, neutrophil accumulation and ER stress were independent of genotype. Protection from Gao-binge injury in Irf3-/- mice was associated with an increased ratio of Ly6Clow (restorative) to Ly6Chigh (inflammatory) cells compared to C57BL/6 and Irf3S1/S1 mice. Reduced ratios of Ly6Clow/Ly6Chigh in C57BL/6 and Irf3S1/S1 mice were associated with an increased apoptosis in the Ly6Clow population in response to Gao-binge. Activation of primary cultures of macrophages with Poly (I:C) induced translocation of IRF3 to mitochondria, association with Bax and activation of Caspases 3 and 9, processes indicative of activation of the RIPA pathway. Conclusions: Taken together, these data identify important contributions of the non-transcriptional function of IRF3 in modulating the innate immune environment in response to Gao-binge ethanol exposure via regulation of immune cell apoptosis. Keywords: etanol, IRF3, innate immune responses, Gao-binge model, alcohol-related liver disease.